SELETIVIDADE DE INSETICIDAS A Trissolcus basalis (WOLL.) (HYM.: SCELIONIDAE) EM LABORATÃ“RIO - Godoy, Karlla Barbosa; Galli, Júlio César; Ãvila, Crébio José; Ferreira, Beatriz Spalding Corrêa (REVISTA DE AGRICULTURA, 2016)
SELETIVIDADE DE INSETICIDAS A Trissolcus basalis (WOLL.) (HYM.: SCELIONIDAE) EM LABORATÃ“RIO